2005
DOI: 10.1177/016173460502700102
|View full text |Cite
|
Sign up to set email alerts
|

3-D Correlation-Based Speckle Tracking

Abstract: Widely-used 1-D/2-D speckle tracking techniques in elasticity imaging often experience significant speckle decorrelation in applications involving large elevational motion (i.e., out of plane motion). The problem is more pronounced for cardiac strain rate imaging (SRI) since it is very difficult to confine cardiac motion to a single image plane. Here, we present a 3-D correlation-based speckle tracking algorithm. Conceptually, 3-D speckle tracking is just an extension of 2-D phase-sensitive correlation-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
103
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 31 publications
0
103
0
Order By: Relevance
“…10,11 Tracking is dependent on image quality and is vulnerable to dropouts of ultrasound data and reverberation. Moreover, some clinical studies have reported that 2D STI has limited feasibility or wide variability in the values for LVrot.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…10,11 Tracking is dependent on image quality and is vulnerable to dropouts of ultrasound data and reverberation. Moreover, some clinical studies have reported that 2D STI has limited feasibility or wide variability in the values for LVrot.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
“…16,23 Three-Dimensional SPI for Rotation Measurement With the advent of real-time 3D ultrasound in echocardiography, 10,11 3D STI using real-time 3D data sets will certainly become increasingly attractive. 24 Chen et al 10 have shown the feasibility of 3D STI on 3D ultrasonic data sets and that 3D STI was better than 2D SPI for cardiac strain imaging. Abe et al 13 have used 3D STI to accurately detect regional radial strain and ejection function in a 3D LV model.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temporal correlations might thus be used as a feature for distinguishing between blood and the heart muscle. For 3D strain imaging purposes, the cross-correlation function (CCF) of 2D windows of rf-data was calculated [8], [9] using two subsequent full volumes. The peak of the crosscorrelation function reveals the displacement of a 2D segment of rf-data in the next time frame in 2D space.…”
Section: Temporal Cross-correlation Of the Radio Frequency Signalmentioning
confidence: 99%